Spatial, Seasonal, and Solar Cycle Variations of the Martian Total Electron Content (TEC): Is the TEC a Good Tracer for Atmospheric Cycles?. Issue 7 (18th July 2018) - Sánchez‐Cano, Beatriz; Lester, Mark; Witasse, Olivier; Blelly, Pierre‐Louis; Indurain, Mikel; Cartacci, Marco; González‐Galindo, Francisco; Vicente‐Retortillo, Álvaro; Cicchetti, Andrea; Noschese, Raffaella
Abstract: We analyze 10 years of Mars Express total electron content (TEC) data from the Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) instrument. We describe the spatial, seasonal, and solar cycle behavior of the Martian TEC. Due to orbit evolution, data come mainly from the evening, dusk terminator and postdusk nightside. The annual TEC profile shows a peak at Ls = 25–75° which is not related to the solar irradiance variation but instead coincides with an increase in the thermospheric density, possibly linked with variations in the surface pressure produced by atmospheric cycles such as the CO2 or water cycles. With the help of numerical modeling, we explore the contribution of the ion species to the TEC and the coupling between the thermosphere and ionosphere. These are the first observations which show that the TEC is a useful parameter, routinely measured by Mars Express, of the dynamics of the lower‐upper atmospheric coupling and can be used as tracer for the behavior of the thermosphere. Plain Language Summary: Ten years of Mars Express total electron content (TEC) data from the Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) instrument are analyzed. The TEC is a parameter that gives information of the amount of free electrons within the ionosphere (ionized layer at 100–200 km). In this study, we describe how the TEC varies along the seasons, planet coverage, and also with the solar activity. We have found that variations in the thermosphere (neutral atmospheric layer between 100 and 200 km) have an effect on the ionosphere, especially notable during spring of the northern hemisphere. With the help of a numerical simulation of the ionosphere‐thermosphere over a Martian year, we have found that Mars' atmospheric cycles can have an effect on the upper atmosphere. Key Points: The spatial, seasonal, and solar cycle variation of 10 years of Mars' TEC is assessed Mars Express routinely measures the dynamic of the thermosphere‐ionosphere coupling The TEC can be used as a tracer for atmospheric cycles on the upper atmosphere